THE REMOTE AND AGILE AUDITING: A FRAUD PREVENTION EFFORT TO NAVIGATE THE AUDIT PROCESS IN THE COVID-19 PANDEMIC - Dwi Koerniawati (Universitas Airlangga, 2021)
This research aims to identify and navigate how auditors are able to find solutions to various obstacles that occurred in the audit process during the Covid-19 pandemic. This study uses a qualitative (non-positivistic) approach with this type of research focusing on systematic exploratory research of a pandemic covid-19 phenomenon and using descriptive analysis techniques and anticipatory condensation data from remote and agility audits. The method of data collection is carried out by interviews, observations and documentation with purposive sampling as a method of selecting research sources. Source triangulation and triangulation techniques are selected by researchers to ensure the validity of the data. The research sources are external and internal auditors from KAP leading in Indonesia and are foreign affiliated audit firm and internal auditors from companies that implement internal control of 5 people. The result of this study is that remote audit and agility audit can be used as a solution to navigate problems in carrying out the audit process and business disruption in the time of the covid-19 pandemic crisis. Remote Audit and Agility audit is an alternative way that can be used as a reference in conducting the audit process during the Covid-19 pandemic to still be able to realize Good corporate governance (GCG) and can quickly detect fraud. Real contributions that can be utilized by auditors are helping auditors find solutions in solving problems such as supervision in the form of asset misappropriation cases ranging from cash theft, misappropriation of cash receipts, fraud during disbursement, misuse of company asset inventory. and theoretical contributions to strengthen and enrich fraud pentagon theory, in addition, this research can also formulate a framework to realize Good corporate governance (GCG) and post crisis such as COVID-19.